Preferensi Muzakki Membayar Zakat Melalui Baitul Mal: Studi Empiris di Kota Banda Aceh - Khairul Amri; Marwiyati Marwiyati (Universitas Batanghari, 2019)
This study aims to analyze the preferences of muzakki paying zakat in Baitul Mal Aceh and the differences in preferences based on socio-demographic characteristics. The study was conducted on 282 muzakki in the city of Banda Aceh. Data collection using a questionnaire and then the data were analyzed using descriptive statistics average method and inference statistics Mann-Whitney test method. The study found that the most determines of muzakki preference in paying zakat through Baitul Mal is the muzakki social environment, followed by Baitul Mal services quality, understanding of zakat management by the institution and the ease of reaching the Baitul Mal location. Mann-Whitney Test different test results indicate that muzakki preferences differ significantly by sex, occupation, and income per month, but not significantly based on age, marital status, and education level.